The Role of Omni-Channel Integration Quality and Perceived Value in Shaping Customer Satisfaction and Loyalty in BCA Basic Banking Services - Lie, Jessica; Yulika Rosita Agrippina (Program MM Universitas Surabaya, 2025)
Purpose: This study aims to examine the impact of omni-channel integration quality and omni-channel perceived value on customer satisfaction, customer satisfaction on customer loyalty, and the mediation of customer satisfaction between omni channel integration quality and omni-channel perceived value to customer loyalty in the context of basic banking services (BBS). BCA offer BBS that is essential for customers. Method: There are 143 respondents, who live in Surabaya, aged above 17 years old, who have used a minimum of two out of four of these BCA channels: ATM BCA, KlikBCA, BCA mobile, and myBCA, and who have used three basic banking services, namely money transfer, checking account balances, and bill payments in the last three months. The data collected using questionnaire, Google Form. Next, it was processed using Smart PLS and analyzed through the Structural Equation Model (SEM) method. Result: The finding of this research proved omni-channel integration quality has a positive and significant impact on omni-channel perceived value, omni-channel integration quality has positive and significant impact on customer satisfaction, omni-channel perceived value has positive and significant impact on customer satisfaction , customer satisfaction mediate the relationship between omni-channel integration quality and customer loyalty, and customer satisfaction mediates omni channel perceived value to customer loyalty.